The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3920/jiff2020.0064
|View full text |Cite
|
Sign up to set email alerts
|

Use of black soldier fly and house fly in feed to promote sustainable poultry production

Abstract: The growing human population, changing dietary habits and intensifying competition between food and feed production underline the urgent need to explore novel sustainable production chains. In the past, the poultry sector has gained popularity due to its superior environmental and economic benefits compared to other livestock production systems. Therefore, it is of special interest to focus on refinement and innovation along the value chain to further improve the sector’s sustainability. One major issue is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 127 publications
1
51
0
Order By: Relevance
“…Poultry Dörper et al (2021) produce a similar evaluation of insects as feed for the poultry industry. They also explored various insect models that can be used presently (e.g.…”
Section: Using Insects As Feedmentioning
confidence: 99%
See 2 more Smart Citations
“…Poultry Dörper et al (2021) produce a similar evaluation of insects as feed for the poultry industry. They also explored various insect models that can be used presently (e.g.…”
Section: Using Insects As Feedmentioning
confidence: 99%
“…Unlike the aquaculture industry, fewer data are available on the use of these insects as feed. Dörper et al (2021) provide an overview of the benefits of insects as feed for the poultry industry ranging from improved animal health to conversion rates across the different sectors (e.g. layers, broilers).…”
Section: Using Insects As Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]. Apart from chitin maggot, BSF also has higher linoleic fatty acids, approximately 0.70%, based on [3]. [4] revealed that linoleic affects cholesterol concentration in eggs.…”
Section: Introductionmentioning
confidence: 97%
“…One of the major advantages of using edible insects is the possible health effects for humans (Stull, 2021) and animals (Gasco et al, 2021). Then, what is the effect of using insects as feed on the target animals: fish (Liland et al, 2021), poultry (Dörper et al, 2021), pigs (Veldkamp and Vernooij, 2021) and pets (Bosch and Swanson, 2021). Food safety deals with biological (Vandeweyer et al, 2021) and chemical (Meyer et al, 2021) contaminants.…”
mentioning
confidence: 99%